Zinc-chromium layered double hydroxide anchored charcoal composite material as well as preparation method and application thereof

By anchoring the biochar composite with zinc-chromium layered double hydroxide, the problem of insufficient adsorption capacity of biochar to arsenic is solved, and the arsenic removal in water is achieved efficiently, and excellent adsorption performance and stability are demonstrated. It is suitable for arsenic pollution Water body repair and arsenic leaching of slag/soil is prevented.

CN119186550AActive Publication Date: 2024-12-27NORTHWEST A & F UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411543242.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-27
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing biochar has limited adsorption capacity of arsenic in water bodies, and the layered double hydroxides limit their adsorption performance due to the tight accumulation of sheets.

Method used

The zinc-chromium layered double hydroxide-anchored biochar composite is used to load the zinc-chromium layered double hydroxide on the biochar to improve its surface functional groups and structural heterogeneity, reduce agglomeration, and enhance adsorption performance.

Benefits of technology

It significantly improves the adsorption effect and stability of arsenic, achieves efficient removal of As(V) and As(III) in water, and shows excellent arsenic pollution repair ability in complex water bodies, and has good recycling potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186550A_ABST
    Figure CN119186550A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional materials for environmental pollutants, in particular to a zinc-chromium layered double hydroxide anchored biochar composite material as well as a preparation method and application thereof. The zinc-chromium layered double hydroxide anchored biochar composite material is prepared according to the following steps: dipping biochar in a mixed solution of a water-soluble zinc salt solution and a water-soluble chromium salt solution, keeping for 0.5-2 hours under the condition that the pH value is 9.5-10.0, aging for 12-48 hours at 60-80 DEG C, washing the obtained product, and drying to obtain the zinc-chromium layered double hydroxide anchored biochar composite material. The adsorption performance on anions can be remarkably improved through the synergistic effect of the layered double hydroxides and the biochar. The composite material shows good adsorption performance on arsenic in a water body, has the characteristics of high efficiency, economy, reusability and the like, and has good engineering application potential in the aspects of repairing the arsenic-polluted water body, reducing leaching of arsenic pollutants in arsenic-containing soil and slag and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials for environmental pollutants, and in particular to a zinc-chromium layered double hydroxide anchored biochar composite material, a preparation method thereof, and an application thereof in repairing an arsenic-contaminated environment or reducing the leaching of arsenic pollutants in arsenic-containing slag / soil. Background Art

[0002] Arsenic (As) is a toxic metalloid that is easily enriched in surface water and groundwater through geochemical cycles. Arsenic exists mainly in inorganic forms of arsenite (As(III)) and arsenate (As(V)) in natural water bodies, soils and slag. Exposure to high concentrations of arsenic can have adverse effects on human health, with a strong risk of carcinogenesis and even instantaneous death at lethal doses. Therefore, it is crucial to seek cost-effective technologies to remove arsenic from water bodies.

[0003] Currently, the technologies used for arsenic purification include adsorption, oxidation and bioremediation. Among them, adsorption technology is considered to be a promising technology because of its economy, effectiveness and ease of operation. Among them, biochar is widely used as an adsorbent in the control of heavy metal pollution in water bodies. However, the surface of biochar mainly carries a net negative charge, and its adsorption capacity for anionic pollutants in water bodies, including As(III) and As(V), is limited. Therefore, modifying biochar is a feasible method to improve its adsorption capacity for anionic pollutants.

[0004] Layered double hydroxides (LDHs) have a large specific surface area, a positively charged layered structure, and exchangeable intercalated anions in the matrix, which have excellent adsorption properties for anionic pollutants and therefore have considerable potential in industrial applications. However, the dense stacking of layered double hydroxides limits the adsorption of pollutants. Summary of the invention

[0005] Based on the above technical problems, the present invention provides a zinc-chromium layered double hydroxide anchored biochar composite material and its application in purifying As(V) and As(III) in pollutants. The composite material provided by the present invention exhibits good adsorption performance for As(V) and As(III) in water, and also exhibits good removal efficiency and stability in practical applications.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing a zinc-chromium layered double hydroxide anchored biochar composite material, comprising the following steps:

[0008] The biochar is immersed in a mixture of a water-soluble zinc salt solution and a water-soluble chromium salt solution, maintained at pH = 9.5-10.0 for 0.5-2 hours, and then aged at 60-80° C. for 12-48 hours. The obtained product is washed and dried to obtain the zinc-chromium layered double hydroxide anchored biochar composite material.

[0009] As a preferred embodiment of the present invention, the molar ratio of the water-soluble zinc salt to the water-soluble chromium salt is 2-4:1.

[0010] As a preferred embodiment of the present invention, the concentration of the water-soluble zinc salt solution is 0.02-0.2 mol / L, the concentration of the water-soluble chromium salt solution is 0.01-0.05 mol / L, and the dosage ratio of the biochar to the mixed solution of the water-soluble zinc salt solution and the water-soluble chromium salt solution is 1-2 g:100 mL.

[0011] As a preferred embodiment of the present invention, the water-soluble zinc salt is selected from zinc nitrate, zinc chloride, zinc sulfate or zinc acetate, and the water-soluble chromium salt is selected from chromium sulfate, chromium nitrate or chromium trichloride.

[0012] As a preferred embodiment of the present invention, the pH is maintained at 9.5 to 10.0 for 0.5 to 2 hours. Specifically, 1 mol / L NaOH and 0.5 to 1 mol / L Na 2 SO 4 The mixed solution is titrated into the mixed solution of water-soluble zinc salt solution and water-soluble chromium salt solution for 0.5 to 2 hours, maintaining pH = 9.5 to 10.0.

[0013] As a preferred embodiment of the present invention, the biochar is prepared according to the following steps:

[0014] The biomass is heated to 550-800°C at a heating rate of 5-10°C / min under a nitrogen atmosphere, and then kept warm for 1-4 hours to obtain the product.

[0015] As a preferred embodiment of the present invention, the biomass comes from sawdust, branches, leaves or grass leaves.

[0016] The present invention also provides a zinc-chromium layered double hydroxide anchored biochar composite material prepared according to the method.

[0017] The present invention further provides an application of the zinc-chromium layered double hydroxide anchored biochar composite material in arsenic pollution remediation or reducing arsenic pollutant leaching in arsenic-containing slag / soil.

[0018] As a preferred embodiment of the present invention, the arsenic is As(V) or As(III).

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention loads and anchors zinc-chromium layered double hydroxide (ZnCr-LDH) on biochar, effectively improving the poor adsorption effect of biochar on anionic pollutants such as As(V) and As(III). In addition, granular / blocky LDH may limit the adsorption of pollutants due to its dense stacking of layers. Using biochar as a carrier can effectively improve its physical and chemical properties, such as surface functional groups, structural heterogeneity, reduced agglomeration and enhanced adsorption performance, thereby improving the adsorption effect of the composite material on As(V) and As(III).

[0021] 2. The biochar prepared by the present invention is an environmentally friendly material with rich pore structure, which provides a good support layer for the load anchoring of zinc-chromium layered double hydroxide (ZnCr-LDH). 2 + :Cr 3+ molar ratio, and the ZnCr-LDH / BC composite material with good adsorption capacity was screened out.

[0022] 3. The ZnCr-LDH / BC composite material prepared by the present invention shows good removal effect in practical applications. The composite material can not only effectively adsorb As(V) and As(III) in water, but also has excellent arsenic pollution remediation ability in complex real water matrix. At the same time, the composite material has good stability, and can still maintain its structural characteristics after As(V) and As(III) adsorption. After four recycling tests, it still has a certain arsenic adsorption capacity, which verifies its potential use in engineering practice.

[0023] 4. The raw materials used in the present invention are solid waste (such as sawdust), which is abundant in source and low in price. It can be used to repair heavy metal pollution in water bodies while realizing resource utilization of solid waste.

[0024] 5. The preparation method provided by the present invention has a simple process, is easy to operate, and the raw materials and required reagents are easy to obtain. No special equipment is required, the production cost is low, and it is conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the scanning electron microscope (SEM) image of the original biochar;

[0026] Figure 2 is a scanning electron microscope (SEM) image of the zinc-chromium layered double hydroxide anchored biochar composite;

[0027] Figure 3 is the X-ray diffraction (XRD) pattern of the zinc-chromium layered double hydroxide anchored biochar composite;

[0028] Figure 4 It is a comparison of the adsorption effects of zinc-chromium layered double hydroxide anchored biochar composite material and original biochar on As(V) and As(III);

[0029] Figure 5 It is the regeneration and recycling of zinc-chromium layered double hydroxide anchored biochar composite material;

[0030] Figure 6 It is the adsorption isotherm fitting of As(V) and As(III) on Zn-Cr layered double hydroxide anchored biochar composite;

[0031] Figure 7 The present invention provides a zinc-chromium layered double hydroxide anchored biochar composite material for preventing arsenic from leaching and diffusion in arsenic-contaminated soil and arsenic-containing slag. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments, which should not be considered as a limitation of the present invention, but rather a more detailed description of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0033] Arsenic (As) is a toxic metalloid that is easily enriched in surface water and groundwater through geochemical cycles. Currently, the technologies used for arsenic purification include adsorption, oxidation and bioremediation. Among them, biochar has been widely used as an adsorbent in the control of heavy metal pollution in water bodies. However, the surface of biochar mainly carries a net negative charge, and its adsorption capacity for anionic pollutants in water bodies, including As(III) and As(V), is limited.

[0034] At the same time, layered double hydroxide (LDH) has a large specific surface area, a positively charged layered structure, and exchangeable intercalated anions in the matrix, which has excellent adsorption properties for anionic pollutants and therefore has considerable potential in industrial applications. However, the dense stacking of layered double hydroxides limits the adsorption of pollutants.

[0035] Based on this, the present invention provides a method for preparing a zinc-chromium layered double hydroxide anchored biochar composite material, comprising the following steps:

[0036] The biochar is immersed in a mixture of a water-soluble zinc salt solution and a water-soluble chromium salt solution, maintained at pH = 9.5-10.0 for 0.5-2 hours, and then aged at 60-80°C for 12-48 hours. The obtained product is washed and dried to obtain a zinc-chromium layered double hydroxide anchored biochar composite material.

[0037] The present invention loads and anchors zinc-chromium layered double hydroxide (ZnCr-LDH) on biochar, effectively improving the poor adsorption effect of biochar on anionic pollutants such as As(V) and As(III). In addition, granular / blocky LDH may limit the adsorption of pollutants due to its dense stacking of layers. Using biochar as a carrier can effectively improve its physical and chemical properties, such as surface functional groups, structural heterogeneity, reduced agglomeration and enhanced adsorption performance, thereby improving the adsorption effect of the composite material on As(V) and As(III).

[0038] Example 1

[0039] A method for preparing a zinc-chromium layered double hydroxide anchored biochar composite material comprises the following steps:

[0040] Step 1: Sawdust from a drum processing plant in Yangling was selected as the biomass raw material for preparing biochar. The sawdust was washed with water, dust removed and naturally dried, placed in a porcelain crucible and transferred to a muffle furnace protected by a nitrogen atmosphere, heated to 800°C at a rate of 10°C / min, kept warm for 4 hours, and finally cooled naturally to room temperature. The obtained biochar sample was washed three times in ultrapure water, dried at 60°C, ground and passed through a 100-mesh nylon sieve for later use.

[0041] Step 2: Add 50 mL of 0.01 mol / L Cr 2 (SO 4 ) 3 ·H 2 O and 50 mL 0.02 mol / L ZnSO 4 7H 2 O solution, 1g of biochar was immersed in the mixed solution, and then 1mol / L NaOH solution and 0.5mol / L Na 2 SO 4 The mixed solution of the solution was titrated into the above solution for about 0.5 h, maintaining pH = 9.5. The solution was then aged at 60°C for 48 h, and the product was washed three times and dried at 60°C, ground and passed through a 100-mesh nylon sieve to obtain a zinc-chromium layered double hydroxide anchored biochar composite material.

[0042] Scanning electron microscopy analysis of the biochar obtained in step 1 and the zinc-chromium layered double hydroxide anchored biochar composite material obtained in step 2 showed that the original biochar without zinc-chromium layered double hydroxide anchoring showed typical biochar porous material characteristics ( Figure 1 ), while the Zn-Cr-LDH-anchored biochar composite material showed a morphology covered by a flower-like structure formed by many nanosheets and anchored on the surface ( Figure 2The composite material was further characterized by X-ray diffraction, and diffraction peaks belonging to the crystal plane of zinc-chromium layered double hydroxide (labeled as ZnCr-LDH) were observed ( Figure 3 ), indicating that ZnCr-LDH has been successfully anchored in biochar.

[0043] Example 2

[0044] A method for preparing a zinc-chromium layered double hydroxide anchored biochar composite material comprises the following steps:

[0045] Step 1: Use tree branches from the campus of Northwest A&F University as biomass raw materials for preparing biochar. Dry the branches naturally, crush them, and then screen the debris with a particle size of less than 2 mm. Put them into a porcelain crucible and transfer them into a muffle furnace protected by a nitrogen atmosphere. Heat them to 700°C at a rate of 8°C / min, keep them warm for 2 hours, and finally cool them naturally to room temperature. Wash the obtained biochar sample in ultrapure water 4 times, dry it at 60°C, grind it and pass it through a 100-mesh nylon sieve for later use.

[0046] Step 2: Add 0.05 mol / L Cr(NO 3 ) 3 and 0.15 mol / L ZnCl 2 Equal amounts were mixed to form a 500 mL mixed solution, 5 g of biochar was immersed in the suspension, and then 1 mol / L NaOH solution and 0.8 mol / L NaOH solution were added under continuous magnetic stirring. 2 SO 4 The mixed solution of the solution was titrated into the above solution for about 1 hour, maintaining pH = 9.8. The solution was then aged at 60°C for 24 hours, and the product was washed 5 times and dried at 60°C, ground and passed through a 100-mesh nylon sieve to obtain a zinc-chromium layered double hydroxide anchored biochar composite material.

[0047] Example 3

[0048] A method for preparing a zinc-chromium layered double hydroxide anchored biochar composite material comprises the following steps:

[0049] Step 1: Select plant residues such as leaves and grass leaves from the campus of Northwest Agriculture and Forestry University as biomass raw materials for preparing biochar, dry them naturally, crush them, sieve them, put them into a porcelain crucible and transfer them into a muffle furnace protected by a nitrogen atmosphere, heat them to 550°C at a rate of 5°C / min, keep them warm for 1h, and finally cool them naturally to room temperature. Wash the obtained biochar sample in ultrapure water 4 times, dry it at 70°C, grind it and pass it through a 100-mesh nylon sieve for later use.

[0050] Step 2: Add 50 mL of 0.02 mol / L CrCl 3The solution was mixed with 20 mL of 0.2 mol / L zinc acetate solution, and 30 mL of ultrapure water was added to a total volume of 100 mL. 2 g of biochar was immersed in the mixed solution, and then 1 mol / L NaOH solution and 0.5 mol / L NaOH solution were added under continuous magnetic stirring. 2 SO 4 The mixed solution of the solution was titrated into the above solution for about 2 hours, maintaining pH = 10.0. The solution was then aged at 80°C for 12 hours, the product was washed 3 to 5 times and then dried at 60°C, ground and passed through a 100-mesh nylon sieve to obtain a zinc-chromium layered double hydroxide anchored biochar composite material.

[0051] Example 4

[0052] Adsorption effect of zinc-chromium layered double hydroxide anchored biochar composites on As(V) and As(III) in water.

[0053] 20 mg of the zinc-chromium layered double hydroxide anchored biochar composites prepared in Example 1, Example 2 and Example 3 were added to 20 mL of a polyethylene centrifuge tube containing 10 mg / L As(V) and As(III) solution at pH = 7, and then shaken at 180 rpm and 25°C for 24 h. The supernatant was filtered through a 0.22 μm nylon filter membrane, and the residual concentrations of As(V) and As(III) in the filtrate were determined using the "Determination of Mercury, Arsenic, Selenium, Bismuth and Antimony in Water Quality - Atomic Fluorescence Method" (HJ-694-2014), and the adsorption of As(V) and As(III) by the composites was calculated.

[0054] like Figure 4 As shown, compared with the original biochar (without ZnCr-LDH anchoring), the zinc-chromium layered double hydroxide anchored biochar composite material prepared by the present invention showed better arsenic removal ability in the experiment, and its adsorption capacity for arsenic was significantly higher than that of the original biochar.

[0055] Example 5

[0056] In order to explore the reusability of the zinc-chromium layered double hydroxide anchored biochar composite material, the composite material prepared in Example 2 was added at a dosage of 1 g / L into a 100 mg / L As(V) solution (pH = 7) and a 10 mg / L As(III) solution (pH = 9). After oscillation at 180 rpm and 25°C for 24 h, the adsorbent was separated by centrifugation, washed with deionized water 3 to 5 times, and 0.1 mol / L NaOH was added as a desorbent. After oscillation at 180 rpm and 25°C for 24 h, the adsorbent was separated again. After washing and drying, the arsenic adsorption and desorption cycle was carried out according to the above steps.

[0057] Regeneration effect of zinc-chromium layered double hydroxide anchored biochar composites Figure 5 As shown in the figure, with the increase of the number of cycles, the removal rate of the composite material for As(V) and As(III) continued to decrease. After four cycles, the adsorption capacity of the composite material for As(V) decreased from 46.73 mg / g to 15.94 mg / g, and the adsorption capacity for As(III) decreased from 5.44 mg / g to 2.04 mg / g. After two cycles, the reuse rate of the composite material for As(V) and As(III) remained at 55.94% and 75.74%, respectively, and after four cycles, it decreased to 34.11% and 37.5%, respectively, which means that the composite material can be reused for the adsorption and purification of As(V) and As(III).

[0058] Example 6

[0059] Removal effect of zinc-chromium layered double hydroxide anchored biochar composite on As(V) and As(III) in actual polluted water bodies.

[0060] 20 mg of the zinc-chromium layered double hydroxide anchored biochar composite prepared in Example 3 was added to a solution of As(V) (20 mL, pH = 7) and As(III) (20 mL, pH = 9) with a concentration of 0.1 to 100 mg / L in a polyethylene centrifuge tube, and then shaken at 180 rpm and 25°C for 24 h. The supernatant was filtered through a 0.22 μm nylon filter membrane, and the residual concentrations of As(V) and As(III) in the filtrate were determined, and the adsorption of As(V) and As(III) by the composite material was calculated, and the following results were obtained: Figure 6 The equilibrium concentration Ce-adsorption amount q is shown e Quantitative curve.

[0061] The results of fitting the curves with Langmuir, Freundclich and Sips models showed that the maximum adsorption capacity of zinc-chromium layered double hydroxide anchored biochar composite materials for As(V) and As(III) can reach 67.45 mg / g and 24.55 mg / g respectively.

[0062] The contaminated water samples were prepared by adding As(V) and As(III) to the real river water, lake water and well water collected. Specifically, As(V) and As(III) were added to make their concentrations 0.12 mg / L. At the same time, the effluent (arsenic-containing wastewater) from a non-ferrous metal processing plant in Xi'an, Shaanxi was also collected to evaluate the practical application potential of the composite material. The chemical composition of the effluent (arsenic-containing wastewater) collected from the non-ferrous metal processing plant was: As(V) = 13.8 mg / L, As(III) = 0.7 mg / L, Cr(III) = 0.081 mg / L, Ni(II) = 2.76 mg / L, Cu(II) = 0.89 mg / L, Pb(II) = 1.021 mg / L, Mn(II) = 0.426 mg / L, pH = 5. In the test, 20 mg of the composite material prepared in Example 3 was added to a polyethylene centrifuge tube containing 20 mL of polluted river water, lake water, well water and non-ferrous metal processing plant effluent (arsenic-containing wastewater), and then shaken at 180 rpm and 25° C. for 24 hours. The results are shown in Table 1.

[0063] Table 1 Treatment effect of composite materials on polluted water and effluent from non-ferrous metal processing plants (arsenic-containing wastewater)

[0064]

[0065]

[0066] According to Table 1, after the polluted river water, lake water and well water were adsorbed by the composite material, the residual arsenic content was lower than the agricultural irrigation water quality standard limit of 0.05 mg / L (GB 5084-2021). After the simulated arsenic-containing wastewater was adsorbed by the composite material, the residual arsenic content was lower than the comprehensive wastewater discharge standard limit of 0.5 mg / L (GB 8978-1996).

[0067] Example 7

[0068] The ability of zinc-chromium layered double hydroxide anchored biochar composites to prevent arsenic leaching from arsenic-containing soils and slag.

[0069] A glass tube with an inner diameter of 1 cm was filled with 4 cm thick high-purity quartz sand fine powder (particle size of about 100 mesh) and flattened and compacted, then filled with 0.5 g of the composite material prepared in Example 1 and flattened and compacted, and then 10 g of arsenic-contaminated soil (provided by this laboratory, soil pH 8.03, total arsenic 45.13 mg / kg, exceeding the limit specified in GB 15618-2018) was added to the glass tube and flattened and compacted, and then 4 cm thick high-purity quartz sand fine powder was added and flattened and compacted, which was recorded as "soil-addition" treatment. For comparison, a similar method was used to conduct a comparative test, namely: a 4 cm thick high-purity quartz sand fine powder (particle size of about 100 mesh) was filled into a glass tube with an inner diameter of 1 cm and flattened and compacted. No composite material was filled, and 10 g of arsenic-contaminated soil was directly added to the glass tube and flattened and compacted. Thereafter, a 4 cm thick high-purity quartz sand fine powder was added and flattened and compacted, which was recorded as the "soil-no addition" treatment.

[0070] In addition, slag leaching tests were also conducted, where the arsenic-contaminated soil in the above test was replaced with arsenic-containing slag (pH 7.83, total arsenic 28.42 mg / kg) provided by a nonferrous metal processing plant in Xi'an, Shaanxi Province, and recorded as "slag-added" treatment and "slag-no-added" treatment respectively.

[0071] After the test device was installed, 30 mL of ultrapure water was added to the experimental system every day. After standing for 1 day, the leaching liquid was collected once and the total arsenic content was measured. The test lasted for 35 days. Figure 7 shown.

[0072] Depend on Figure 7 It can be seen that during the 35-day leaching test, arsenic continued to appear in the leachate of the "soil-no addition" treatment and the "slag-no addition" treatment, while no obvious arsenic was detected in the "soil-addition" treatment and the "slag-addition" treatment due to the presence of the zinc-chromium layered double hydroxide anchored biochar composite material. This shows that the zinc-chromium layered double hydroxide anchored biochar composite material has the ability to prevent arsenic from arsenic-contaminated soil and arsenic-containing slag from leaching and diffusion.

[0073] The experiments of the above-mentioned related embodiments show that the method provided by the present invention significantly improves the removal effect of As(V) and As(III) by anchoring ZnCr-LDH to biochar, and has strong adsorption performance for As(V) and As(III). At the same time, the composite material also shows excellent practical water application potential and good regeneration ability, and the zinc-chromium layered double hydroxide anchored biochar composite material can be used as an efficient and easy-to-prepare adsorbent, and has good engineering application potential in the remediation of arsenic-contaminated water bodies, reducing the leaching of arsenic pollutants in arsenic-containing soils and slags, etc.

Claims

1. A method for preparing a zinc-chromium layered double hydroxide anchored biochar composite material, characterized in that: The following steps are involved: The biochar is immersed in a mixture of a water-soluble zinc salt solution and a water-soluble chromium salt solution, maintained at pH = 9.5-10.0 for 0.5-2 hours, and then aged at 60-80° C. for 12-48 hours. The obtained product is washed and dried to obtain the zinc-chromium layered double hydroxide anchored biochar composite material.

2. The method for preparing the zinc-chromium layered double hydroxide anchored biochar composite material according to claim 1, characterized in that: The molar ratio of the water-soluble zinc salt to the water-soluble chromium salt is 2-4:

1.

3. The method for preparing the zinc-chromium layered double hydroxide anchored biochar composite material according to claim 2, characterized in that: The concentration of the water-soluble zinc salt solution is 0.02-0.2 mol / L, the concentration of the water-soluble chromium salt solution is 0.01-0.05 mol / L, and the dosage ratio of the biochar to the mixed solution of the water-soluble zinc salt solution and the water-soluble chromium salt solution is 1-2 g: 100 mL.

4. The method for preparing the zinc-chromium layered double hydroxide anchored biochar composite material according to claim 1, characterized in that: The water-soluble zinc salt is selected from zinc nitrate, zinc chloride, zinc sulfate or zinc acetate, and the water-soluble chromium salt is selected from chromium sulfate, chromium nitrate or chromium trichloride.

5. The method for preparing the zinc-chromium layered double hydroxide anchored biochar composite material according to claim 1, characterized in that: The biochar is prepared according to the following steps: The biomass is heated to 550-800°C at a heating rate of 5-10°C / min under a nitrogen atmosphere, and then kept warm for 1-4 hours to obtain the product.

6. A zinc-chromium layered double hydroxide anchored biochar composite material prepared according to the method according to any one of claims 1 to 5.

7. Use of the zinc-chromium layered double hydroxide anchored biochar composite material according to claim 6 in arsenic pollution remediation.

8. Use of the zinc-chromium layered double hydroxide anchored biochar composite material according to claim 6 in reducing the leaching of arsenic pollutants in arsenic-containing slag or soil.

9. The use according to claim 7 or 8, characterized in that: Arsenic is pentavalent arsenic or trivalent arsenic.

Citation Information

Patent Citations

  • Preparation method of layered double hydroxide-loaded biochar composite material

    CN108837803A

  • Preparation method and application of Fe-Mg / mulberry stem biochar composite material

    CN112007609A

  • Zirconium oxide doped magnetic high-surface activated carbon composite material, preparation method and application thereof

    CN112774625A

  • Sulfur-based intercalated hydrotalcite modified charcoal-based adsorption material and preparation and application thereof

    CN114082403A

  • Aminated magnetic microsphere-carbon base-layered double hydroxide composite material as well as preparation method and application thereof

    CN116272918A